A Comparative Study of Seminal Plasma and Blood Serum Macro and Trace Elements in the the Breeding (October) and the Non-Breeding (April) Seasons in Merino Ram - BULBUL, B.; AKALIN, P. P.; BAŞPINAR, N.; BUCAK, M. N.; KIRBAŞ, M.; ÖZTÜRK, C.; GÜNGÖR, S.; AKBULUT, K. (Journal of the Hellenic Veterinary Medical Society, 2019)
In this study, it was aimed to investigate the concentrations of macro and trace elements in seminal plasma and blood serum in the breeding (October) and the non-breeding (April) seasons in Merino Ram. Nineteen Merino Rams, aged 18-24 months, were involved in the study. Blood (once) and ejaculate samples (6 replicates) were taken in the breeding (October) and the non-breeding (April) seasons. Blood serum, seminal plasma and diet Calcium, Sodium, Potassium, Magnesium, Phosphorus, Sulfur, Zinc, Selenium, Chrome, Manganese, Nickel, Molybdenum and Boron concentrations were determined by ICP-AES. In blood serum, Sodium and Selenium concentrations were higher (p<0.05 and 0.001, respectively) in the the breeding season than in non-breeding season, whereas Potassium, Chromium and Boron concentrations were lower (p<0.05, 0.001 and 0.001, respectively) in the breeding season than in the non-breeding season. In seminal plasma Calcium, Sodium, Zinc and Manganese concentrations were higher (p<0.05, 0.001, 0.01 and 0.05, respectively) in the breeding season than in the non-breeding season, whereas Phosphorus, Chrome, Molybdenum and Boron concentrations were lower (p<0.001, 0.001, 0.05 and 0.001, respectively) in the breeding season than in the non-breeding season. No difference was detected regarding the other elements. The higher levels of Cr and B in the non-breeding season compared to the breeding season both in serum and seminal plasma, regardless of diet intake, suggest that these elements may play a crutial role on male fertility in Merino Ram.